(untitled) (Pedagogy of Higher and Secondary Education, 2011)
Intruction of elements of the adaptive system of instruction during realization of the lab works in mathematical statistics in institutes of higher education with technical specialization assists conservation of the semantic strees of the course and activation of independet cognitive activity of students.